Distribution and Function of Neuropeptides W/B Signaling System - Chottova Dvorakova, Magdalena (Frontiers in Physiology, 2018)
Neuropeptide W (NPW) and neuropeptide B (NPB) are two structurally and functionally related regulatory peptides, which are highly expressed in several brain regions and, additionally, in some peripheral tissues. Nevertheless their distribution within the tissues is not similar. They act on target tissues via two subtypes of G protein-coupled receptors, either NPBWR1 (known also as GPR7) or NPBWR2 (GPR8) with different binding affinities. NPB specifically activates NPBWR1, whereas NPW activates both the receptors with equal potency. Both these peptides are involved in the central regulation of neuroendocrine axes, energy homeostasis, feeding behavior, cardiovascular functions, circadian rhythm, pain sensation, modulation of inflammatory pain, and emotions. In recent years, studies have shown that NPB takes a part in sleep regulation, while NPW participates in regulation of vascular myogenic tone, inhibits gastric tension sensitive vagal afferents and insulin secretion. Expression of NPW in the stomach is regulated by meal. These findings reveal the diversity in functions of NPW/NPB signaling system, which are reviewed here together with mapping of expression of this signaling system members.